Repetição de Tarefa de Tradução, Memória de Trabalho e Desempenho Oral em L2 - Paula, Socorro Gardenia Carvalho de (2020)
Translation Studies are a recent discipline that has taken shape since the 80's in Brazil, and has been occupying a prominent place as a field of study of FL, raising a question about the importance of using translation in the classroom. A pedagogical approach to translation has been done through tasks. Task-Based Language Teaching (TBLT) has been seen by authors such as Ellis (2003), Bygate, Skehan and Swain (2001) as an effective approach in language teaching and learning. Based on this assumption, the use of a translation task through the L2 narrative of images can contribute to this process. Within the task study, a construct that also attracts considerable attention emerges: planning as a form of preparation for the performance of the already mentioned tasks, allowing a more controlled language processing with more sophisticated results in terms of complexity, accuracy and fluency. Thus, one of the ways to achieve effective planning would be through task repetition, where the first realization of a task is seen as a form of planning for a second encounter with the same task. Therefore, this study intends to investigate the relationship between working memory capacity and oral performance in L2 using the repetition of a translation task. More specifically, it investigates whether the repetition of a translation task leads to significant differences in the oral performance of L2, as described in several studies (BYGATE, 2001; GASS, MACKEY, ALVAREZ-TORRES & FERNANDEZ-GARCIA, 1999; KIM & TRACY VENTURA, 2013; LYNCH & MCLEAN, 2000; PATANASORN, 2010, D’ELY 2006,among others). In addition, since the benefits of planning may depend on the ability to actually recover what was planned and implement such information in the new performance of the task (ORTEGA, 2005), the present study also aims to investigate which individuals, if with higher or lower working memory capacity, retrieve more information from the first encounter with a translation task and implement this information when repeating it. It also investigates which individuals, whether with higher or lower working memory capacity, benefit most from the repetition of the translation task in terms of fluency, accuracy and complexity. A population of 30 students from “Casa de Cultura Britânica” underwent data collection which consisted of a working memory test, a translation task repeated twice and two questionnaires. In general, the results showed that the repetition of the translation task led to significant gains in terms of fluency and accuracy, but not in complexity. In addition, it also showed that the percentage of information retrieved from the first encounter with the translation task and implemented in the second encounter was statistically the same for both groups of higher and lower memory capacity. The results also indicated that for the variable accuracy (% of error-free clauses), the individuals in the group with the lowest memory showed, on average, significantly higher gains compared to the group with the highest memory, suggesting that participants with lower memory benefited more from the repetition of the translation task. The results were discussed in the light of the literature in the fields of Task-Based Language Teaching, translation tasks, task repetition, working memory and speech production. Pedagogical implications were also pointed out suggesting that task repetition can be a valuable pedagogical tool to promote benefits in the students' oral performance as it allows the development of both meaning and form of the language to be learned.